Scientific publication of master's degree works of a graduate school in Peru. in Peru - Mamani Benito, Oscar (2021)
Introduction: Master’s theses are expected to contribute to scientific knowledge; therefore, it is important that they are published in indexed scientific journals. Objective: To determine the frequency of scientific publication of master’s theses from a graduate school in Peru. Method: Descriptive study of document analysis in 307 theses approved in the period 2010 - 2019, from business sciences, health sciences, psychology, human sciences and education, engineering and architecture, public health and theology. Results: There is a predominance of non-experimental design studies (79.5%) and correlational type (64.8), in addition, only 11.07% were published in scientific journals, of which, one is indexed in Scielo and two in Scopus. Conclusion: the frequency of publication of master’s theses of a Graduate School in Peru is low, and its impact on the international scientific community is even lower